2013
DOI: 10.1002/cjce.21835
|View full text |Cite
|
Sign up to set email alerts
|

Role of asphaltenes in stabilisation of water in crude oil emulsions

Abstract: Even though asphaltenes do not have the well‐defined amphiphilic structure characteristic of surfactants, it has been shown that they can stabilise water‐in‐oil emulsions. We propose that this stabilisation occurs because asphaltene aggregation results in the formation of a network within the thin oil film separating approaching emulsified water droplets. This network changes the rheology of the film to non‐Newtonian, which prevents drainage of the film at thicknesses less than about 50–100 nm. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 31 publications
9
64
0
Order By: Relevance
“…We did not observe formation of precipitates for 40 wt.% solutions and apparent sediment was formed at the bottom of vials for 5 and 11 wt.% solutions. This observation agrees with previously reported value for critical S/B ratio in case of heptol (80:20) S/B ratio 11,18,21,27. As the initial precipitates formed in the solution at bitumen…”
supporting
confidence: 94%
See 1 more Smart Citation
“…We did not observe formation of precipitates for 40 wt.% solutions and apparent sediment was formed at the bottom of vials for 5 and 11 wt.% solutions. This observation agrees with previously reported value for critical S/B ratio in case of heptol (80:20) S/B ratio 11,18,21,27. As the initial precipitates formed in the solution at bitumen…”
supporting
confidence: 94%
“…11,18,21,27 Such non-Newtonian behavior of the film liquid was proposed to be a new mechanism for stabilization of water in oil emulsions. The experiments that showed such non-Newtonian behavior were performed for a similar system and concentrations as the system studied in this work.…”
Section: Newtonian Behavior Of Bitumen Solutions As We Mentioned In mentioning
confidence: 99%
“…It was reported that rather than whole asphaltenes, only a subfraction of asphaltenes is more likely the real contributor to the stabilization of W/O emulsions. 26,[80][81][82][83][84][85][86] The asphaltenes adsorbed onto clays have also been found to be different in composition from whole asphaltenes. 70,[75][76][77] Therefore, it is important to find ways to extract and study these particular species from asphaltenes, which are mainly responsible for the relevant issues of interest.…”
Section: Extended-sara (E-sara)mentioning
confidence: 99%
“…It was suggested that the interfacial rigidity is due to the crosslinking of asphaltene aggregates. 3,13,14 Recently, Czarnecki et al [15][16][17] argued that the general belief that the whole asphaltene fraction is responsible for emulsion stabilization, and the wide use of SARA terminology 18 in the emulsion stability context are in fact impeding the progress in understanding petroleum emulsions stability. These authors suggested that "only a small fraction of asphaltenes are in fact involved in the emulsion stabilization".…”
Section: Introductionmentioning
confidence: 99%